2021
DOI: 10.21203/rs.3.rs-808321/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Kinesio Taping on Low Back Pain During Pregnancy: A Systematic Review and Meta-Analysis

Abstract: Background: Low back pain during pregnancy affects the normal daily activities of pregnant women to a certain extent. Current studies have shown that Kinesio Taping(KT) may be a treatment for low back pain during pregnancy, but there is still a lack of key evidence. The purpose of this study is to evaluate the efficacy and safety of KT in the treatment of low back pain during pregnancy.Methods: PubMed, Web of Science, The Cochrane Library, Wanfang Data, CNKI, and VIP databases were searched to collect randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…We will apply the Grading of Recommendations Assessment, Development and Evaluation (GRADE) method to evaluate the level of confidence in regards to outcomes. [18,19] Two independent reviewers will conduct the assessment. In most cases, disagreements were resolved by discussion between the 2 researchers.…”
Section: Search Strategymentioning
confidence: 99%
“…We will apply the Grading of Recommendations Assessment, Development and Evaluation (GRADE) method to evaluate the level of confidence in regards to outcomes. [18,19] Two independent reviewers will conduct the assessment. In most cases, disagreements were resolved by discussion between the 2 researchers.…”
Section: Search Strategymentioning
confidence: 99%
“…If p > 0.10, I 2 < 50%, which indicates that the studies are homogeneous, fixed effect model analysis should be selected. If p < 0.10, I 2 > 50%, which indicates heterogeneity among the studies, random-effect model analysis should be selected [25]. The level of meta-analysis is set to p < 0.05.…”
Section: Data Analysis and Synthesismentioning
confidence: 99%
“…Once we looked up the review articles on KT published over the past 5 years through the Medical Literature Analysis and Retrieval System Online (MEDLINE) (accessed via PubMed), a total of 52 studies were identified. Most of 52 studies are on cerebral palsy [13][14][15], low back pain [16][17][18][19][20][21][22][23], ankle functional performance [24][25][26], knee osteoarthritis (OA) [27][28][29][30][31][32][33], shoulder pain and disability [34][35][36][37][38], breast lymphedema [7,39], rehabilitation after stroke [40][41][42] and so on; however, there are only four studies related to edema [43][44][45][46]. Therefore, the purpose of this study was to review the literature on KT for reducing edema caused by musculoskeletal disorders and investigate whether the use of KT have any effects on controlling edema.…”
Section: Introductionmentioning
confidence: 99%